The Relationship Between Self-Concept and Social Interaction Among Nursing Students - Veronica Paula; Edson Kasenda; Sry Rezeky Simamora; Desty Monica Pasaribu; Vevia Revana Batunanggar; Deborah Siregar (Universitas Pelita Harapan, 2025)
Self-concept and social interaction are important factors in the development of nursing students' professional skills. A positive self-concept can enhance students’ ability to engage in effective social interactions, which plays a vital role in building strong interpersonal relationships within academic and clinical practice environments. This study aimed to examine the relationship between self-concept and social interaction among nursing students at a private university in Tangerang. This study employed a quantitative correlational method with a cross-sectional approach. A total of,302 nursing students from a private university in Western Indonesia were selected using a quota sampling technique. The instruments included the Tennessee Self-Concept Scale (TSCS) and the Social Interaction Psychology Scale, both of which were utilized in their validated Indonesian-language versions. Data analysis using Spearman’s rank correlation was conducted to examine the relationship between self-concept and social interaction. The findings showed that most students had a moderate level of self-concept (64.9%) and social interaction (73.2%). Spearman’s rank correlation analysis revealed a significant positive correlation of moderate strength between self-concept and social interaction among nursing students. This suggests that students with a better self-concept tend to demonstrate more effective social interaction. Therefore, educational institutions are encouraged to develop programs aimed at enhancing both self-concept and social interaction to support students’ academic performance and professional development.